Curricular conversations : play is the (missing) thing - Macintyre Latta, Margaret, 1955- (Studies in curriculum theory, 2012)
"The central theme of Curricular Conversations is this: Play is the thing that brings aesthetic curricular complications near educators and their students, making the lived consequences very vivid, tangible, and possible. Viewing curriculum as genuine inquiry into what is worth knowing, rather than simply a curricular document, this book explores the significances instilled and nurtured through aesthetic play. Each chapter delves into the space a given artwork reveals. The artworks act as points of departure and/or generative vehicles, foregrounding the roles and possibilities of play within curricular conversations. Looking at relevant educational issues, traditions, and theorists through an illuminating lens, this book speaks to curriculum theorists and arts educators everywhere"--